PENGARUH KECERDASAN EMOSIONAL, KECERDASAN SPIRITUAL DAN MOTIVASI KERJA TERHADAP KINERJA GURU SEKOLAH MUHAMMADIYAH KOTA TARAKAN - Dian Sandi Utama; Syahran; Milwan (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
The quality of educational institutions is important to note as a place to create thenation's generation. Its quality is determined by how well the performance of theteachers. The position of the teacher becomes very important because not onlyteaches knowledge but also build student character. Meanwhile, there are severalfactors that can affect the performance. This study aims to analyze the effect ofemotional intelligence, spiritual intelligence and work motivation on theperformance of Muhammadiyah school teachers in Tarakan City.The researchsample amounted to 92 teachers based on sample calculations using the Isaac andMichael formula with sampling technique simple random. The instrument used is aquestionnaire. The research data was processed using multiple linear analyses andtabulated with the IBM SPSS Statistics 25 program. The results showed thatemotional intelligence and work motivation had an effect on performance, whilespiritual intelligence had no effect on performance.